Topical Insulin Eye Drops: Stability and Safety of Two Compounded Formulations for Treating Persistent Corneal Epithelial Defects - Marta Vicario-; Virginia Puebla-García; Lidia Ybañez-García; José Javier López-Cano; Miriam Ana González-; Marco Brugnera; Bárbara Burgos-Blasco; David Díaz-Valle; José Antonio Gegúndez-Fernández; José Manuel Benítez-; Rocío Herrero-Vanrell (MDPI AG, 2024)
Compounded insulin eye drops were prepared at 1 IU/mL from commercially available subcutaneous insulin by dilution in saline solution or artificial tears. Physicochemical characterization and in vitro tolerance testing in human and conjunctival cells were followed by a 28-day short-term stability study under various conditions. The formulations were isotonic (280-300 mOsm/L), had a pH close to neutral (7-8), medium surface-tension values (<56 MN/m−1), and low (≈1 mPa·s) and medium (≈5 mPa·s) viscosities (compounded normal saline solution and artificial tear-based preparation, respectively). These values remained stable for 28 days under refrigeration. Microbiological stability was also excellent. Insulin potency remained in the 90-110% range in the compounded formulations containing normal saline solution when stored at 2-8 °C for 28 days, while it decreased in those based on artificial tears. Although both formulations were well tolerated in vitro, the compounded insulin diluted in a normal saline solution exhibited better cell tolerance. Preliminary data in humans showed that insulin in saline solution was an effective and safe treatment for persistent corneal epithelial defects. Compounded insulin eye drops diluted in normal saline solution could, therefore, constitute an emergent therapy for the treatment of persistent corneal epithelial defects.